Introducing www.epidemic-em.org: a collection of online resources and training materials for strengthening use of emergency operations centers for epidemic response - Banaski, James; Govender, Nevashan; Groome, Michelle J.; Houser, Ryan; Greiner, Ashley; Krishnan, Sharanya; Means, Brenna; Remmel, Ryan; Alvarado, Ileana Vélez; Standley, Claire J. (Disaster medicine and public health preparedness, 2024)
Objective:This work aimed to demonstrate that a website, www.epidemic-em.org, encompassing “static” resources, and videos, as well as other tools, can be used to strengthen public health emergency management capacity during epidemic response.Methods:Existing resources were updated and developed for self-directed Emergency Operations Centers’ capacity strengthening, in order to encompass current best practices, and to emphasize how public health emergency management concepts can support epidemic response activities. These materials formed the core of the website, launched in June 2020, to which country case studies were added. In 2021, a pilot virtual training program was designed using recorded video lectures and interviews with global experts in addition to the website material, which was delivered to South African responders.Results:The website has been accessed in more than 135 countries, demonstrating widespread reach and interest in online and freely accessible materials to support public health emergency operations. Over 30 people participated in the pilot virtual training, and the evaluation showed improvement in knowledge, confidence in using emergency management concepts for epidemic response, and positive feedback on the virtual modality.Conclusions:Online tools can expand access to materials and resources for public health emergency management capacity strengthening. Virtual modalities can further serve as a powerful complement, and perhaps replacement, for traditional in-person technical assistance, despite some limitations.
Gesehen am 21.08.2024